Conclusion [In The Economics of Teff] - Minten, Bart; Taffesse, Alemayehu Seyoum; Brown, Petra (International Food Policy Research Institute, 2018)
By any measure, teff is an important crop in Ethiopia. It is estimated that one-fifth of all land under cultivation in the country, approximately 2.7 million hectares, is used to grow teff. However, while teff has been grown and consumed in Ethiopia for centuries, relatively little is known about the economics of teff production and the postfarm teff value chain that supplies this staple to millions. This is set to change with more time and effort being devoted to building the value chains surrounding its production, marketing, and consumption in various ways. People in government, agriculture, health, research, and other areas are becoming more aware that by increasing teff productivity through research, application, and training, this drive could turn around the lives of many poor people in rural communities.